1994
DOI: 10.1002/ijc.2910590303
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed expression of insulin‐like growth factor binding protein‐1 mRNA in the endometrium: A molecular mechanism associating endometrial cancer with its risk factors

Abstract: The insulin-like growth factor (IGF) system is thought to function as a mediator of steroid hormone actions in the endometrium. IGFs (IGF-I and IGF-II) are also potent mitogens in endometrial cancer. The biological actions of IGFs are modulated by specific binding proteins (IGFBP)--6 cloned and sequenced so far--which may either inhibit or enhance the effects of IGF at the cellular level. In the endometrium, IGFBP-1 gene expression is stimulated by progesterone and inhibited by insulin, while IGFBP-1 inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 26 publications
0
44
0
1
Order By: Relevance
“…In addition to these studies, one large case-control study showed an increase in endometrial cancer risk in postmenopausal women (Troisi et al 1997) with elevated serum levels of C-peptide. A similar but much smaller study also showed higher fasting insulin levels in thirty-two postmenopausal patients with endometrial cancer compared with eighteen controls (Rutanen et al 1994).…”
Section: Chronic Hyperinsulinaemia and Cancer Riskmentioning
confidence: 73%
“…In addition to these studies, one large case-control study showed an increase in endometrial cancer risk in postmenopausal women (Troisi et al 1997) with elevated serum levels of C-peptide. A similar but much smaller study also showed higher fasting insulin levels in thirty-two postmenopausal patients with endometrial cancer compared with eighteen controls (Rutanen et al 1994).…”
Section: Chronic Hyperinsulinaemia and Cancer Riskmentioning
confidence: 73%
“…Progesterone, on the other hand, is widely accepted as a protective factor against endometrial carcinogenesis due to its antiproliferative effects on endometrial tissue by promoting a local increase in IGF binding protein 1 (IGFBP) synthesis. Insulin manifests its carcinogenic characteristics by increasing the bioactivity of IGF1 while also downregulating the synthesis of IGFBP1 in endometrial tissue (Murphy & Ghahary 1990, Rutanen et al 1994. Furthermore, chronic hyperinsulinemia may lead to ovarian hyperandrogenism, and increased peripheral aromatization of androgens to estrogen may increase the risk of endometrial cancer, particularly in postmenopausal women (Kaaks et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Among them seven genes have been reported previously as differentially expressed in endometrial tumors. Lactotransferrin (LTF) was upregulated (Walmer et al, 1995), whereas six genes including SFRP4, DCN, IGFBP6, HGF, WT1 and WNT4 were downregulated in the endometrial tumors (Rutanen et al, 1994;Bui et al, 1997;Yoshida et al, 2002;Muller-Tidow et al, 2003;Smid-Koopman et al, 2004;Acs et al, 2004;Hrzenjak et al, 2004). Of these genes, only WT1 was been specifically associated with endometrioid cancer (Acs et al, 2004).…”
Section: Discussionmentioning
confidence: 99%